COMPANY COMPETITIVENESS - S.N. Abieva,; L.K. Matkarimova, (Academic Journal of Physical and Chemical Sciences, 2019)
The article is concerned with the theory that the companies run in competitive environment within the market economy conditions what is a market immanent feature ensuring quality product output in buyer’s demand.Besides, the article considers substantial differences between a company and its category of product competitiveness. As such, in his work the author emphasizes the essential features of competitive capacity of enterprises. Given recommendations on reaching up the competitiveness. The conclusion is drawn thatkeeping up with other companies is provided by all elements of marketing that an enterprise possess. The production and effective sale of competitive goods is the summarizing indicator of enterprise viability.